A Research on the Separation of Sand out of Cassava Slurry by Cyclone - Le, Khanh Dien; Vu, Dinh Hai (Applied mechanics and materials, 2023)
Monosodium Glutamate (MSG) [1] was invented more than 100 years ago from its first invention in 1908 by Japanese biochemist Kikunae Ikeda, who was trying to isolate and duplicate the savory taste of kombu, an edible seaweed used as a base for many Japanese soups. From 2016, most MSG worldwide is produced by bacterial fermentation in a process similar to making vinegar or yogurt. Sodium is added later, for neutralization. During fermentation, Corynebacterium species, cultured with ammonia and carbohydrates from sugar beets, sugarcane, tapioca (cassava tuber) or molasses, excrete amino acids into a culture broth from which L-glutamate is isolated. In this process, Monosodium Glutamate companies buy cassava [2] pulps from farmers that contain a lot of sand and impurities. In order to increase the productivity with lowest expense, the filtration of sand and solid impurities’ is performed by separation cyclone. In this paper, we study all the measure to design a system of effective pump, cyclone to extract as much as possible all of solid impurities included sand out of cassava slurry before providing to the bacterial fermentation in a process.